The Qur’anic Concept of Khalifah and the Ecology of Mizan: Interpreting Environmental Crisis Through Classical and Modern Tafsir - M. Bahroni Arifin; Mailatu Habibatir Rahmah; Qomariatul Wardaniyah; Moh. Nurun Alan Nurin PK (Journal of Islamic Thought and Contemporary Studies, 2025)
The concept of Khalifah (Caliphate/Vicegerency) in the Qur'an holds a fundamental position as a moral and theological mandate for humanity to be the steward of the Earth, not its absolute owner.This mandate is realized through the task of isti‘mār, which is the constructive development and prosperity of the Earth, yet still within the limits of mizan the principle of cosmic balance that encompasses both ecological and social dimensions. Violations of this principle result in fasad, or corruption on land and sea, which is a direct consequence of the misuse of human power.This study employs a thematic tafsir (exegesis) approach by examining both classical and contemporary interpretations. Classical tafsir, such as the works of al-Ṭabari, al-Qurṭubi, and Ibn Kathir, emphasize humanity's theological and moral responsibility to Allah. In contrast, contemporary tafsir from scholars like Fazlur Rahman Quraish Shihab, Fazlun Khalid, Seyyed Hossein Nasr, and Ziauddin Sardar interprets the concept within the context of ecological ethics and sustainable development.The integration of these perspectives demonstrates that ecological responsibility is an integral part of the khalifah trusteeship. Consequently, the current global environmental crisis can be seen as a form of modern humanity's failure to maintain the mizan and fulfill the role of khalifah as stipulated in the Qur'an.